Psychometric Properties of Self-Report Questionnaire-20 (SRQ-20) Indonesian Version - Clement Eko Prasetio; Airin Triwahyuni; Ahmad Gimmy Prathama (Jurnal Psikologi, 2022)
The prevalence of mental disorders experienced by the global community, including in Indonesia, is increasing steadily. It is thus necessary to have a time-efficient and valid screening measuring tool as a basis to provide appropriate treatment to mental disorders. The Self-Report Questionnaire-20 (SRQ-20) is a screening tool that is often used in Indonesia to identify mental disorder symptoms. However there is limited study that has attempted to discover the SRQ-20 factors and conducted a construct validity test on them. The purpose of this study was to investigate factors and test the construct validity of SRQ-20 developed by the World Health Organization (WHO). There were 674 students involved in the study. Exploratory factor analysis was used to discover the factors. Evidence based on internal structure using a confirmatory factor analysis was also collected. Findings revealed five factors for the SRQ-20, these are energy, cognitive, depression, physiological, and anxiety. The five factor model is an alternative for classifying symptoms on the SRQ-20. This way, symptoms on the SRQ-20 can be grouped into five factors, of which can assist clinicians take more appropriate and faster action. Findings also revealed, however, that the construct validity of the five factor model needs is less than the one factor model. Therefore, for further research, using a wider population to check the stability of structure across developmental age. SRQ-20 could also be compared with the gold standard measurement to get a predictive validity.